Experimental study of Yushania alpina bamboo fiber - Muluken Awulachew Asres; Girma Zerayohannes; Adil Zekaria; Denamo Addissie Nuramo (Materials Research Express, 2024)
The characteristics of bamboo fiber depend on the source species. This study investigated the properties of Yushania alpina bamboo fibers extracted using mechanical, chemical, and combined methods. Samples from each extraction method were tested for tensile strength. Scanning electron microscopy was used to examine the morphology of the fibers. Fourier transform infrared was used to trace functional group changes. The absorption capacity of the fibers was also examined. The thermal properties of the fibers were investigated using thermogravimetric analysis. The chemical compositions of the fibers were studied using a gravimetric method. In contrast to mechanically and combinedly extracted bamboo fibers, chemically extracted fiber had up to 90.84% and 67.06% increments in tensile strength, respectively. Scanning electron microscopy revealed the removal of attachments on the surfaces of the fibers extracted chemically. The diameter of the fibers extracted chemically was reduced. Fourier transform infrared showed no change in functional groups among the extracted fibers. However, lignin content was reduced in chemically extracted fibers. The absorption capacity of the fibers was encouraging for use in composites. Thermal analysis showed improved thermal properties with the chemical method. Chemical analysis revealed reduced lignin and hemicellulose compositions in chemically extracted fibers. This study suggests bamboo fibers can be used in the construction industry for sustainability.